Impact of Employee Retention Strategies on Employee Loyalty in Select it Companies at Hyderabad – An Empirical Study - Dr. C. Lalitha, Dr. V. Parvathi (International Journal of Advanced Science and Technology, 2020)
Purpose of the study: The purpose of this study to understand the theoretical framework of Employee Retention Strategies and Employee Loyalty and also study the impact of employee retention strategies on employee loyalty specific to the select IT companies in Hyderabad.